(3dWGFa GdeZGfi aj GdaQb Hjf GdCZGfj hGdeZGfis - (3afj , eMeO Hf EHQGgjes
(3ChdgG (B:s
(3OYJfi KdGKI CSHGH dgPG GdJMQjQ GdeSJWGH , GdChd Cf GdCZGfi gi GdZhGfi hgj Cf GdZdWI Hd GdSbWI s
(3BNQgG (B:s
(3adYeQi dh QCi GHf MLI JYHjQi Yf GdeZGfi hJYHjQ Cgd GddZI dbGd (B: (3eG CMSf JYHjQ afi YfOi heG CHdZI fLR JCdjagG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B193 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs